Silver Nanoparticles and Antibiotics: A Promising Synergistic Approach to Multidrug-Resistant Infections - Eudald Casals; Muriel F. Gusta; Neus Bastus; Jordi Rello; Victor Puntes (Microorganisms)
The escalating threat of antibiotic resistance demands innovative strategies against multidrug-resistant (MDR) microorganisms, particularly in hospital settings where such infections represent a major global health challenge. Since the rapid growth of nanotechnology interdisciplinary research and funding programs in the 2000s, silver ions have re-emerged as potent antimicrobial agents, offering a promising complement to conventional therapies. This therapeutic potential is nowadays explored through the use of silver nanoparticles (AgNPs) as sources for silver ions release. Recent studies have shown that controlled silver ion release enhances the efficacy of common antibiotics. This can be attributed to the energetically demanding nature of the bacterial response to silver, which weakens bacterial metabolism and, in turn, overwhelms bacterial defenses and increases antibiotic effectiveness. Herein, historical insights into the use of colloidal silver and AgNPs are combined with a review of recent research on the exploitation of the synergistic effect between AgNPs and antibiotics as a promising strategy against MDR pathogens.